CO Pollution Warning System for Indoor Parking Area Using FPGA - Prima Dewi Purnamasari; Evan G. Sumbayak; Vicky Dwi Kurniawan; RR. Wulan Apriliyanti (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
From some compounds used as parameters in air pollution-such as O3, Particulate Materials, CO, NO2, SO2 and Pb-CO is the most common cause of poisoning accidents. Indoor parking area is one sample of potential area for CO pollution. However, according to the scientific nature of CO-tasteless, colorless, and odorless-people exposed to CO are usually not aware that s/he exposed to dangerous levels of CO. This research aimed to make a prototype of an embedded system that can monitor air pollution, give an effective warning and it should be affordable. The prototype of CO air pollution alert system has been successfully built using FPGA Xilinx Spartan 3E as the major component. Sensor Hanwei MQ7 used in this prototype has been tested in a simulation box using cigarette smoke as CO pollutant and the reading result has met the characteristic curve in the datasheet. The system interface has met user satisfaction with MOS value 4.31 from 5 scales. Based on the response time testing, we conclude that FPGA is suitable to be used in a system that performs fast parallel processing based on logical actions from the input given.